MODERN ROLE OF STAKEHOLDERS IN UKRAINIAN LAND AND ENVIRONMENTAL MANAGEMENT - Alina Lizunova; Olga Petrakovska; Mariia Mykhalova (Acta Scientiarum Polonorum. Formatio Circumiectus)
Aim of the study: The development of land relations in Ukraine towards European integration requires the identification of all interested parties involved in the management of land resources and nature use. Since all existing directions of land use, as one of the main components of natural resources, can have an impact on the current state of the environment, land management is considered as a component of general environmental management.